STRENGTHENING THE SUPERVISION OF MARKET CONDUCT OF BANKING FINANCIAL SERVICES BY FINANCIAL SERVICE AUTHORITY (OJK) IN CENTRAL JAVA - Sulistyandari, S; Said, Noor Aziz; Hastuti, Wiwik Yuni (Jurnal Dinamika Hukum, 2016)
This study aims to assess and find weaknesses regulation and supervision of market conduct banking financial services, and find weaknesses supervision of market conduct banking financial services in the region of Central Java and offer for solutions. The results show that Financial Service Authority/FSA (known as OJK) LawÂ  and POJK No.01/POJK.07/ 2013 are the governing authority of the OJK under the supervision of market conduct financial services. Until present, BI Law and Banking Law have not set about it. In the future market surveillance authorities conduct financial services under the authority of BI and the OJK, these two institutions share in accordance with the authority given to legislation. Supervision of market conduct banking financial services by the OJK overall is only implemented by the Office of Central OJK. While the OJK in Central Java has new obligations education and service consumer complaints so the protection of consumers of financial services has not been optimally implemented at the Central Java OJK office. Keywords : financial market conduct, OJK, supervision